2020
DOI: 10.1016/j.heliyon.2019.e03109
|View full text |Cite
|
Sign up to set email alerts
|

Annual incidences and predictors of 30-day readmissions following spontaneous intracerebral hemorrhage from 2010 to 2014 in the United States: A retrospective Nationwide analysis

Abstract: Objective: 30-day readmission rate is a quality metric often employed to represent hospital and provider performance. Currently, little is known regarding 30-day readmissions (30dRA) following spontaneous intracerebral hemorrhage (sICH). The purpose of this study was to use a national database to identify risk factors and trends in 30dRAs following sICH. Patients and methods: 64,909 cases with a primary diagnosis of sICH were identified within the Nationwide Readmission Database (NRD) from 2010 through 2014. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Data on readmission costs of ICH were identified in 11 studies (Table 6 and Appendix Supplemental Table 8 ) [ 29 , 35 , 36 , 40 , 45 48 , 55 , 56 , 62 , 68 ], although one of these studies provided readmission costs only for both intracerebral and subarachnoid hemorrhage (SAH) [ 47 ]. In a 12-month follow-up period, the all-cause intracerebral hemorrhage readmission costs per patient were reported by Lee et al [ 47 ] in Taiwan ($4102), Meretoja et al [ 48 ] in Finland ($5009), and Goere et al [ 46 ] in Canada ($5905).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on readmission costs of ICH were identified in 11 studies (Table 6 and Appendix Supplemental Table 8 ) [ 29 , 35 , 36 , 40 , 45 48 , 55 , 56 , 62 , 68 ], although one of these studies provided readmission costs only for both intracerebral and subarachnoid hemorrhage (SAH) [ 47 ]. In a 12-month follow-up period, the all-cause intracerebral hemorrhage readmission costs per patient were reported by Lee et al [ 47 ] in Taiwan ($4102), Meretoja et al [ 48 ] in Finland ($5009), and Goere et al [ 46 ] in Canada ($5905).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 44 reviewed studies, six focused on readmission costs as their primary study objective, while the remaining studies provided a global assessment of stroke or post-stroke care costs [ 28 , 37 , 47 , 56 , 67 , 68 ]. Stein et al [ 67 ] was the only one that identified readmission after IS in another hospital as a predictor of increased readmission charges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have analyzed unstratified ICH populations to determine the specific risk factors and readmission rates and reasons. Thirty-day readmission rates in the US national studies were reported as 12-14% and top readmission reasons included cerebrovascular and infectious etiologies [9,10]. Given the reported differences in ICH etiologies for different age groups and high costs associated with unplanned readmissions, it is important to delineate factors that affect ICH etiology and outcomes.…”
Section: Introductionmentioning
confidence: 99%